Metabotropic Glutamate Receptor 7: A New Therapeutic Target in Neurodevelopmental Disorders - Fisher, Nicole M.; Seto, Mabel; Lindsley, Craig W.; Niswender, Colleen M. (Frontiers in Molecular Neuroscience, 2018)
Neurodevelopmental disorders are characterized by a wide range of symptoms including delayed speech, intellectual disability, motor dysfunction, social deficits, breathing problems, structural abnormalities and epilepsy. Unfortunately, current treatment strategies are limited and innovative new approaches are sorely needed to address these complex diseases. The metabotropic glutamate receptors are a class of G protein-coupled receptors that act to modulate neurotransmission across many brain structures. They have shown great promise as drug targets for numerous neurological and psychiatric diseases. Moreover, the development of subtype-selective allosteric modulators has allowed detailed studies of each receptor subtype. Here, we focus on the metabotropic glutamate receptor 7 (mGlu7) as a potential therapeutic target for neurodevelopmental disorders. mGlu7 is expressed widely throughout the brain in regions that correspond to the symptom domains listed above and has established roles in synaptic physiology and behavior. Single nucleotide polymorphisms and mutations in the GRM7 gene have been associated with idiopathic autism and other neurodevelopmental disorders in patients. In rodent models, existing literature suggests that decreased mGlu7 expression and/or function may lead to symptoms that overlap with those of neurodevelopmental disorders. Furthermore, potentiation of mGlu7 activity has shown efficacy in a mouse model of Rett syndrome. In this review, we summarize current findings that provide rationale for the continued development of mGlu7 modulators as potential therapeutics.